Impact of financial development and credit information sharing on the use of trade credit: Empirical evidence from Pakistan - Nisar Ahmad; Mian Sajid Nazir; Bilal Nafees (Cogent Economics & Finance, 2018)
Pakistan is an emerging economy and characterized by a less developed financial system where trade credit is extensively used by listed manufacturing firms (LMFs). This study is focused to investigate the effect of financial development (FD) and credit information sharing (CIS) on the trade credit used by LMFs. For this purpose, dynamic panel model is estimated by applying system GMM (two-step) estimator on the financial data of 327 manufacturing firms listed in PSX Pakistan for the period 2005-2015. Results of the study reveal that FD and CIS have significant effect on the use of trade credit by LMFs in Pakistan. It is found that increase in financial depth increases the supply of funds to the private sector, and resultantly suppliers provide more trade credit to LMFs. While in response to increase in the lending rate, suppliers reduce the transfer of costly funds to LMFs through trade credit. Furthermore, negative relationship between CIS and the use of trade credit is in accordance with the substitution hypothesis. Results of the study have practical implications for the managers of firms and policy makers alike.
Keywords: 330; trade credit financing; financial development; credit information sharing; listed manufacturing firms; system GMM